Fungos isolados de sirênios e cetáceos no brasil: uma abordagem fenotípica, genotípica, diagnóstica e de virulência - Carvalho, Vitor Luz (2015)
The aim of this study was to isolate Sirenia fungi and cetaceans in Brazil to investigate phenotypic aspects, genotypic, diagnostics and virulence. Thus, it was collected with sterile swabs, oral cavity material, nostril / blowhole, genital opening and / or rectum of 104 animals, including 50-manatees of-Amazon (inunguis Trichechus), 33 manatees Navy ( T. manatus), 13 porpoises-red (Inia geoffrensis), three dwarf sperm whales (Kogia sima), two dolphins head-to-melon (Peponocephala electra) a pygmy sperm whale (K. breviceps), a sperm whale (Physeter macrocephalus) and a humpback whale (Megaptera novaeangliae). Among these animals, one Amazonian manatee eight manatees navy had suspected ringworm skin lesions, performed skin scrapings. The swabs were plated onto Sabouraud agar plates containing chloramphenicol, maintained at 37 ° C for five days, while skin scales were seeded in tubes containing Sabouraud agar with chloramphenicol at 25 ° C for ten days. The yeasts were identified by biochemical tests, micromorphology, automated system Vitek, PCR, RFLP and / or sequencing as filamentous fungi were identified by the macro and micromorphology. The strains of Candida spp. (N = 114) obtained were subjected to the broth microdilution test for evaluation of the sensitivity profile to antifungals itraconazole, fluconazole and amphotericin B and the test production of virulence factors (phospholipases, proteases and biofilm). Yeast C. albicans species were submitted to molecular typing by MLST. Two cases of skin surface mycoses in sirenians been diagnosed, a mixed levedurose by C. tropicalis and Trichosporon asahii and a case phaeohyphomycosis by Bipolaris hawaiiensis, and an outbreak of Fusarium (Fusarium sp.). 155 strains were isolated, and 112 inunguis T. (40 Candida albicans, 14 C. parapsilosis strictly speaking, 3 C. metapsilosis, 4 C. orthopsilosis, 9 C. guilliermondii, C. pelliculosa 3, 2 C. tropicalis, 2 C . glabrata, C. famata, 1, 1 C. krusei, C. norvegensis 1, C 1 Ciferri, 22 Trichosporon sp., 6 T.asahii, 2 Rhodotorula sp., Cryptococcus laurentii 1) T. manatus 29 (12 C. albicans, C. tropicalis,4 4 C. famata, C. guilliermondii 3, 1 C. krusei, 1 Rhodotorula sp., 2 R. mucilaginosa, R 1 minute, 1 Trichosporon sp.) and 14 cetaceans (6 C. tropicalis, C. parapsilosis 2, 2 C. famata, 1 Candida sp., 3 Cryptococcus sp.). The minimum inhibitory concentrations (MICs) to amphotericin B ranged from 0.03 to 1μg / ml, resistant strains were observed. The MICs of itraconazole and fluconazole ranged from 0.03 to 16 g / ml and 0.125 to 64 mg / ml, respectively, and found resistance to at least one drug in 34.2% of the isolates, especially C. albicans and C. tropicalis. As for the virulence factors tested, 50% phospholipases produced with high frequency in C. albicans; 50% produced proteases, with a higher prevalence in C. albicans and C. tropicalis; and 35% produced biofilm in varying scales, with higher prevalence in C. tropicalis, and C. orthopsilosis. Molecular typing was performed with 45 strains of C. albicans, yielding genotypes from six clades among the 18 species existing for varying according to the host and geographic location. Based on the above, this study represents a systematic, multidisciplinary contribution about mycology aquatic mammals.